ANALYSIS OF THE ACCURACY OF DOSES OF CEFADROXIL AND CEFIXIME ANTIBIOTICS BASED ON ADULT AGE AT K-24 PASAR MINGGU PHARMACY FOR THE PERIOD JUNE - DECEMBER 2023 - Rizka Novia Arofi; Dwi Puspita Sari; Bunga Destiyana (Bajang Institute, 2025)
Antibiotics are drugs used to prevent and treat bacterial infections that cause disease in living things, especially humans. Various infectious diseases that occur can be handled properly through proper and rational administration of antibiotics. One of the indicators of rationality in the use of antibiotics is the accuracy of dosage. The accuracy of the dose measured in this study is the right amount of medicine, the right way of use, the right dose, the right frequency of administration and the right duration of use. The purpose of this study was to determine the percentage of dose accuracy and inaccuracy in patients who received prescriptions for cefadroxil and cefixime antibiotics at Apotek K-24 Pasar Minggu. This research is a quantitative descriptive observational research with restrospective method. The research sample was 79 prescriptions of patients who received cefadroxil and cefixime antibiotic therapy with adult age at Apotek K-24 Pasar Minggu in the June-December 2023 period. The results of dose accuracy obtained are the right amount of medicine (91.1%), the right way of use (100%), the right dose (96.2%), the right frequency of administration (82.3%), the right duration of use (94.9%).